AN ASSESSMENT OF LAND USE SURROUNDING HYDROPOWER RESERVOIRS USING REMOTE SENSING IN SARAWAK, MALAYSIA - Joan Alicia, Joseph Blandoi; Mohd. Azizul Hafiz, Jamian; Mohd Azlan Jayasilan, Abdul Gulam Azad (UMT, 2020)
The existence of a complex river system in Sarawak has contributed to the abundance of its water resources. The State is drained by 22 major river basins and has a combined installed capacity of hydropower potentials of approximately 20,000 MW of sustainable energy. However, little has been documented on land use around these hydropower dams. The current study is aimed at understanding the general land usecomposition surrounding the existing and planned hydropower reservoirs in Sarawak. The land uses surrounding these dams are expected to influence the livelihood, water discharge and water quality of the dams. A total of ten sites were selected and land use surrounding these study sites identified using Remote Sensing and Geographic Information System tools. Temporal assessment on land-use changes was only conducted for Batang Ai. The study found that a total of six sites have higher forest cover (> 50%) compared to built-up and agricultural lands and showed that 85% variation in built-up land is explained by reservoir area. Agricultural land has increased at the mean rate of 2.25% within 500 metres distance from Batang Ai reservoir shoreline. The findings of this study will hopefully contribute to the knowledge of hydropower reservoir planning and management.